Do Demographic Variables Affect the Organizational Cynicism Levels in Tourism? - Aksu, Akin; Deveci, Irem (Journal of Tourism Management Research, 2019)
This study aimed to determine whether organizational cynicism levels of Generation X and Generation Y employees in tourism sector differed. In this context, the effects of demographic variables on organizational cynicism levels of generation X and generation Y employees were investigated. Quantitative research methods were employed in the study. The population of the study consists of 192 employees of 5-star hotel enterprises that are located and in business in Belek, Antalya region. A significant difference was found between the responses of Generation Y employees and those of Generation X employees. The cognitive, affective and behavioural sub-dimensional and overall organizational cynicism scores of Generation Y employees were determined to be higher than those of Generation X. Generation X employees who want to be part of the organization they work for, and who are strictly committed to their jobs, hardworking, more traditionalist, respectful to authority, diligent and obedient can generally accept the policies of the organization without questioning, employees of Generation Y who do not like bureaucracy and seriousness, who want to manage themselves and take responsibility for themselves, and see the organization as a means and question everything, and who are more individualist can criticise them easily when they are not satisfied, and reflect this on their attitude and behaviour. It is seen that studies that examine the relationship between personal characteristics and organizational cynicism are limited in the relevant literature.